Between Regulation and Media Literacy: Moroccan Public Policies in the Face of Digital Disinformation - KERROUDI Mariam; RAZKAOUI Yassin (Journal of Social Science and Human Research Studies, 2026)
Digital disinformation spreads rapidly on social media and online platforms, posing a major challenge for Moroccan citizens (CESE, 2023). In light of this situation, it is essential to understand how government initiatives can strengthen citizens' media literacy and critical thinking skills (HACA, 2021). This study therefore asks: to what extent do the actions undertaken by the Moroccan state contribute to developing citizens' capacity to identify and evaluate online information? It also contributes to the discussion on public policies for regulating digital information in Morocco by offering a critical analysis of current initiatives. It should be noted that this study focuses on public policies and institutional mechanisms rather than citizens' social practices, which constitutes an explicit limitation of its analytical scope. To answer this question, the research relies on a document analysis of official reports published between 2018 and 2024 by the Ministry of Youth, Culture and Communication, as well as a qualitative analysis of regulatory measures and awareness campaigns undertaken within the framework of the national digital transformation strategy. The corpus comprises twelve official documents and press releases relating to the fight against disinformation and the promotion of digital culture, notably from the High Authority for Audiovisual Communication (HACA), the Economic, Social and Environmental Council (CESE), and other institutions. The analysis highlights several concrete initiatives implemented by the Moroccan state to combat disinformation and strengthen media literacy. These include collaboration with TikTok to reduce the spread of false information and protect user privacy; the establishment of a national strategy to safeguard Morocco's image, including monitoring international media and producing reports on false information; and the drafting of a bill to penalize the dissemination of false information online, thereby strengthening the legal framework. Furthermore, the CESE (2023) indicates that 93% of Moroccans have already been exposed to false information, while 51% admit to having shared disinformation, and 30% state that it is difficult to verify the reliability of a source. The CESE report highlights that government actions are primarily focused on legal regulation, particularly through Laws 88-13 and 447-2, while a more limited number of initiatives address continuing education and public awareness. These legal frameworks provide, for example, for fines for disseminating false news (Article 72 of Law 88-13) and prison sentences for spreading false allegations online (Article 447-2 of the Penal Code). These findings underscore real progress, but also persistent challenges, such as unequal access to digital tools, the need to improve coordination among relevant institutions, and the management of public perceptions of certain media outlets. In conclusion, the study proposes avenues for improvement: strengthening the critical thinking skills of young citizens through educational initiatives and media literacy awareness programs; strengthening collaboration between media outlets and public institutions, particularly through fact-checking platforms such as “Tahaqaq” and the “True or False” initiative launched by SNRTnews; and promoting a responsible and participatory digital culture, in line with the 2030 National Cybersecurity Strategy. These measures aim to equip Moroccan citizens to navigate a complex digital environment autonomously and critically.